Pengaruh Kinerja Keuangan dan Corporate Governance terhadap Penghindaran Pajak - Sartika Wulandari; Rachmawati Meita Oktaviani; Sunarto; Widhian Hardiyanti (Universitas Sains dan Teknologi Komputer, 2023)
Tax avoidance is a strategy that aims to minimize corporate tax on pre-tax profit. This study aims to provide empirical evidence regarding the effect of company size, profitability, independent commissioners, and institutional ownership on tax evasion during the Covid-19 pandemic. The population in this study are manufacturing sector companies listed on the Indonesia Stock Exchange for the 2020-2021 period. By using purposive sampling technique, data were obtained from 74 companies so that 148 observations were obtained. This study shows the results that manufacturing sector companies listed on the IDX during the pandemic period, namely 2020-2021, several factors from financial performance and corporate governance influence the company's tax avoidance actions. The financial performance represented by the variable firm size and profitability shows a positive effect on tax evasion. In corporate governance, independent commissioners and institutional ownership have a negative effect on tax avoidance.